(3GdaUhd aj GdWHs - (3ehSi Hf YHjO Gddg Hf ejehf GdbQWHj, CHh YeQGf,J (B601 (3g` s ((3jhSa Hf YHO GdHQ s)
(3ChdgG (B:s
(3GdMeO ddg bGd GdajdSha GdChMO CHh YeQGf ehSi Hf YHjO Gddg GdbQWHi (B: (3cKjQkG eG Cda GdfGS JhGdjakG s
(3BNQgG (B:s
(3gh GZdX eeG jMJfO Hg NQe djZJPi Hg , hgPG GdeYfi (B( (3GdeYfi (B) (3ghGdPi dMX YfO cdGeg ai GdMjdI , ajJCed gPG s
(3GdfSNI HgG MhGTs
(3GdhQbJjf GdChdi hGdKGfjI JQLY Edi GdbQf GdSGHY ddgLQIs
(3YdjgG ghGeT hJYdjbGJ HYVgG HGdYHQGfis
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs